Strategi Penciptaan Nilai Pada Produk Mikro Bank Syariah Indonesia (Studi Kasus Bank Syariah Indonesia Kantor Wilayah Jakarta Tahun 2021-2022) - Rura, Guntur; Findi, Muhammad; Suprayitno, Gendut (MANAJEMEN IKM: Jurnal Manajemen Pengembangan Industri Kecil Menengah, 2023)
BSI has a strong commitment to MSME to improve, grow and continue to develop. One form of BSI support for MSME is by distributing financing to the micro business segment. The aims of the research are (1) to formulate internal strengths and weaknesses, as well as external opportunities and threats, (2) to determine business strategies that can be implemented, and (3) to explain strategies that will be used to influence customer decisions in selecting micro products at BSI. Jakarta area. Determination of respondents by purposive sampling, with consideration of those who master the problem, totaling five people from BSI management, practitioners and academics. Data analysis with Internal Factor Evaluation (IFE), External Factor Evaluation (EFE), Internal-External (IE) and Strengths, Weaknesses, Opportunities and Threats (SWOT) matrices. and Quantitative Strategic Planning Matrix (QSPM) to determine strategic priorities. The results of the identification of internal strategy factors found that the main strength of BSI Jakarta regional office in distributing microfinance was an easy and fast financing process with a total score was 0.49. The main weakness that affects the microfinance distribution process at the BSI Jakarta regional office is the lack of Islamic banking literacy with a total score is 0.28. The large number of people who do not have an Islamic bank account is the main opportunity with a total score is 0.47. The main threat to BSI's Jakarta regional office in distributing microfinance is the strong existence of conventional banks with a total score is 0.33. The positioning of the IE matrix strategy is based on the results of the total IFE values weighted on the x-axis and the total values of the EFE matrix on the y-axis. The total value of the IFE matrix is 3.01 and EFE matrix is 2.63. This value shows the position of BSI Jakarta regional office in the distribution of micro-financing located in cell IV, namely growth and development.